Adaptasi Teknologi Canva dalam Menunjang Pembelajaran di SMK Negeri 5 Palangka Raya - Merce Masriani Zalukhu; Desti Arini Putri; Mellysa Caldera; Himalia Himalia; Maria Patricia Dolita Doni; Grace Yulita; Irga Loti Rante; Frich Rudolf Turnip; Michael Kentaro Lendrawan; Eldy Marcelino Agusto Soekah; Albertus Niko Liswanto; Afdhal Hafid; Neny Fidayanti; Pujihastuty Pujihastuty (I-Com: Indonesian Community Journal, 2025)
The independent learning campus independent program, one of which is the campus teaching activity is a from community service carried out by students to apply knowledge and apply it in the community environment. MBKM group 2 aims to make a positive contribution to community development, especially towards students. This activity involves various methods, including observation, interviews, and implementation of community empowerment programs. Student collaborate with the local community to identify needs and design appropriate solutions. Adapting technology using canva is one of the easy things for students and provides a lot of creativity through these activities. The result of this activity show an increase in public awareness of the importance of education and health and are a way for students or teachers to utilize technology. The programs implemented have succeeded in attracting active community participation and have a positive impact on daily life. MBKM group 2 has succeeded in achieving its goals in empowering the community and improving the quality of life. It is hoped that this activity can continue and become a model for further MBKM programs.